LncRNA FGD5-AS1 accelerates cell proliferation in pancreatic cancer by regulating miR-520a-3p/KIAA1522 axis. Issue 3 (4th March 2021) - Lin, Jing; Liao, Shasha; Liu, Zewa; Li, E; Wu, Xiaohua; Zeng, Wanting
ABSTRACT: In recent years, FGD5 antisense RNA 1 (FGD5-AS1) was confirmed to be the long non-coding RNAs (lncRNAs) that could accelerate the development of multiple cancers. Nevertheless, specific biological functions and latent mechanism of FGD5-AS1 were not yet clear in pancreatic cancer (PC). This research was aimed to search the functions of FGD5-AS1 on the PC progression. The expression of FGD5-AS1 in PC cells was tested by using RT-qPCR assay. Colony formation assay, EdU assay, flow cytometry assay and transwell assay as well as western blot were adopted to test the cell abilities of proliferation, apoptosis and migration, separately. Furthermore, RIP experiment and pull down assay were applied for validating the correlation FGD5-AS1, miR-520a-3p and KIAA1522. As a result, the abnormal high expression of FGD5-AS1 was observed in PC cells. And cell proliferative and migratory abilities could be restrained via FGD5-AS1 depletion. Moreover, FGD5-AS1 was proven to combine with miR-520a-3p directly. It was also confirmed that KIAA1522 could be targeted by miR-520a-3p. Rescue assay results indicated that overexpressed KIAA1522 could reverse the repressive function of silencing FGD5-AS1 on PC progression. Taken together, FGD5-AS1 accelerated cell proliferation and migration via sponging miR-520a-3p and upregulating KIAA1522.